Analyzing the Behavior of Classical Functionally Graded Coated Beam - Toudehdehghan A.; Rahman M.M.; Tarlochan F. (EDP Sciences, 2023)
Beams and girders; Functionally graded materials; Euler-Bernoulli; Functionally graded; Functionally graded material (FGM); Governing equations; Homogeneous layers; Mechanical loads; Principle of virtual displacements; Static behaviors; Exponential functions